Cetaceans as Ocean Health Indicators of Marine Litter Impact at Global Scale - Fossi, Maria Cristina; Baini, Matteo; Simmonds, Mark Peter (Frontiers in Environmental Science, 2020)
Marine litter is a growing concern for marine animals, including cetaceans for which there is a developing body of evidence showing impacts of both entanglement and ingestion. Better understanding is needed of the current and predicted scales of impacts on cetacean species of both macro- and micro-litter. Some emerging methodological approaches, such as the ‘threefold approach’, will help address data gaps. The relationship between this form of pollution and some cetaceans is strong and the particular feeding habits, and widespread distribution of two whale species means that they can be proposed as ocean health indicators for macro- and micro-litter impacts at global scales, helping steer research. The species concerned are sperm whales, for macro-litter at depth, and fin whales, for micro-debris. Once appropriate techniques have been fully developed for non-lethal assessment, other whale species might also be used as indicators of litter pollution in their specific feeding zones.